Microbiological contamination of vegetables from poultry waste manure: A case study of peri-urban vegetable production in Grand-Popo, Benin - ATIDEGLA, CAPO SÉRAPHIN COCOU; AGBOSS, KOSSI EULOGE; GLELE KAKAÏ, A. ROMAIN LUCAS; HUA, Joël (My University, 2010)
The farmers in grand-Popo in Benin increased vegetable yields with the use of 20 to 50 t .ha-1 of poultry manure and more than 1 t.ha-1 for inorganic fertilizers (NPK and urea). This metod of yield intensification leads to increased sanitaion risks due to the contamination of environment and vegetables by fecal germs (Midmore and Jansen, 2003). A market gardening trial was performed in 2009 in order to test this hypothesis.